Climate Change and Emerging Vector-Borne Diseases in India: editorofijlpr@gmail.com-Epidemiology for better health - Bordoloi, Bobita; Saharia, Samujjal (International Journal of Life Science and Pharma Research, 2021)
Climate change is considered as one of the greatest threats to human health by the World Health Organization. Climate change occurs as a result of both natural and human causes which directly impacts human health through extreme climatic conditions, air quality, sea level rise etc. There is an increasing evidence about the impact of climate change on Vectorborne Diseases (VBDs). Vector-borne diseases account for over 17% of all infectious diseases. Environmental change disturbs the ecological balance thus changing the context within which disease hosts or vectors and parasites breed, develop and transmit disease resulting in the emergence and re-emergence of different VBDs. India is endemic for six major vector-borne diseases namely Malaria, Dengue, Chikungunya, Visceral Leishmaniasis, Japanese Encephalitis and Lymphatic Filariasis. If we fail to reduce the adverse effects and adapt to climatic change then future changes are likely the same. Therefore, a better understanding of climate change and its effects on public health is necessary. Emphasis should be laid on new strategies for the prevention and control of vector-borne diseases. We collected secondary data from published articles, journals and reports on this issue to discuss the impacts of climate change on VBDs. This review aims to discuss the distribution, reasons of emergence and reemergence of important VBDs and its association with climate change highlighting the changing epidemiology of the most important VBDs in India.The objective of this review is to summarize the studies conducted to examine the association between climate change and VBDs and to give suggestions for future research directions.